Constructing Territorial Identity: Strategic Narrative in Aceh’s Maritime Boundary Disputes - Bustami, Bustami; Arifin, Zainal; Samosir, Hasrat Efendi (KARSA Journal of Social and Islamic Culture, 2025)
Territorial disputes concerning maritime boundaries have grown increasingly intricate in the context of subnational autonomy, especially in areas with special administrative status. The communication strategies employed by the Aceh government regarding maritime territorial claims exemplify a distinctive instance of strategic narrative construction within Indonesiaâ€™s decentralized governance framework. This study investigates how the Aceh government formulates strategic narratives in territorial claims, scrutinizing the discursive patterns, rhetorical strategies, and power dynamics inherent in their political communication related to maritime boundary disputes. This research utilizes Critical Discourse Analysis (CDA) in accordance with Faircloughâ€™s three-dimensional framework, examining official documents, press statements, and public speeches delivered by Aceh government officials from 2018 to 2024. The data were subjected to analysis through textual examination, discursive practice evaluation, and contextualization of social practices. The analysis uncovers three predominant narrative strategies: (1) historical legitimacy narratives that invoke pre-colonial sovereignty, (2) legal-constitutional narratives that underscore special autonomy rights, and (3) economic security narratives that emphasize resource sovereignty. The government employs particular linguistic devices, including metaphorical expressions, intertextuality, and strategic ambiguity, to construct legitimacy while addressing multiple audiences. Aceh’s strategic narrative construction illustrates a sophisticated discursive management of territorial claims within constitutional limitations. The findings enhance the understanding of subnational political communication in territorial disputes and provide insights for conflict resolution through narrative mediation.